Bridging Digital Skill Gaps in Vocational Education: A Study on English Teachers' Digital Pedagogical Competencies - Zhang , Guanghui; Policarpio, Princess (International Journal of Education and Humanities, 2025)
This study examines the digital pedagogical competencies of English teachers at Liaocheng Vocational and Technical College, particularly emphasizing their digital literacy, technology integration in teaching, and effective use of digital resources. In response to the increasing demand for digital skills in education, the research aims to identify the current levels of digital proficiency among these educators, analyzing factors such as age, gender, educational background, and teaching experience that may influence their abilities. Adopting a descriptive quantitative methodology, the study uses descriptive statistics to assess teachers' expertise with digital tools, highlighting their capability to incorporate technology into pedagogical practices. The findings reveal a high level of digital proficiency among the teachers surveyed. Specifically, they demonstrate strong digital literacy skills, an effective pedagogical integration of technology, and an adeptness in managing and utilizing digital resources in their teaching processes. These results align with prior studies suggesting that digital skills enhance teaching effectiveness and foster student engagement in modern educational settings. Despite these strengths, the study also identifies potential areas for growth, including the development of personal online presences and the integration of social media platforms for educational purposes. The study’s conclusions underscore the importance of continued professional development in digital pedagogy for vocational educators, recommending targeted training programs to support these teachers in refining their digital skills. This improvement would enable them to effectively support student learning outcomes, contributing to more dynamic and engaging educational experiences.